2019
DOI: 10.1186/s40694-019-0078-5
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the small GTPase rac1 in Trichoderma reesei provokes hyperbranching and impacts growth and cellulase production

Abstract: Background Trichoderma reesei is widely known for its enormous protein secretion capacity and as an industrially relevant producer of cellulases and hemicellulases. Over the last decades, rational strain engineering was applied to further enhance homologous and heterologous enzyme yields. The introduction of hyperbranching is believed to increase protein secretion, since most exocytosis is located at the hyphal apical tip. There are several genetic modifications which can cause hyperbranching, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…When racA was deleted, the mycelial tip increased by about 20%, the number of secreted vesicles increased, and the secretion of glucoamylase increased 4 times as compared to the wild type strain (Fiedler et al, 2018). Similarly, deletion of racA resulted in a hyperbranched phenotype and three folds increase of cellulase activity in T. reesei (Fitz et al, 2019).…”
Section: Regulation Of Mycelium Morphologymentioning
confidence: 98%
“…When racA was deleted, the mycelial tip increased by about 20%, the number of secreted vesicles increased, and the secretion of glucoamylase increased 4 times as compared to the wild type strain (Fiedler et al, 2018). Similarly, deletion of racA resulted in a hyperbranched phenotype and three folds increase of cellulase activity in T. reesei (Fitz et al, 2019).…”
Section: Regulation Of Mycelium Morphologymentioning
confidence: 98%
“…lipolytica, can switch to either yeast form or pseudohyphae and hyphae when exposed to various extracellular environmental stresses (e.g., temperature, pH, mechanical stress, osmotic pressure, carbon, and nitrogen source). Industrial fermentations often run under stress conditions, including high temperatures and osmotic pressures or nutrient deficiency, which may induce the switch to hyphal growth . The mycelial morphology affects the viscosity and efficiency of mass and oxygen transfer in the fermentation broth. Compared with pseudohyphae and hyphae, single yeast forms are easy to manipulate and are metabolically more active than mycelia in submerged cultures . Therefore, cell morphological changes are highly unfavorable for industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Our ndings demonstrated that the Ras small GTPase RSR1 negatively regulates cellulase expression through the ACY1-cAMP-PKA pathway and transcription factors, including cre1, ace3, and xyr1, and that the deletion of RSR1 can increase cellulase production. Previous studies have shown that Ras2 promotes the expression of cellulase genes [37], while rac1 represses it [51], suggesting that the pathway of action of small GTPases is a multichannel circuit. In the future, overexpression of the Ras2 gene or knockout of rac1 in the RSR1 deletion strain will be conducted to determine whether there are interactions between three small GTPases.…”
Section: Discussionmentioning
confidence: 98%